Inovasi Dan Tantangan Perbankan Syariah Pada Era Digital Di Indonesia - Januariansyah Arfaizar; Navirta Ayu; Fitri Riyanto; Yusdani Yusdani; Selamat Muliadi (WADIAH, 2023)
Transactions in sharia banking are currently the people's choice because their products are based on sharia with an element of benefit. Currently is the momentum for Islamic banking to fix problems that occur in transactions to gain more public trust and develop the potential possessed by Islamic banking. This study aims to examine transactions in Islamic banking and their problems. By using qualitative research methods and types of literature study research. This study explains that transactions in Islamic banking have 5 rules, namely useful, fair, pleased, honest and pious. This study also found that in sharia banking transactions there were several internal problems in the form of inadequate human resources, sharia economic regulations, unsupportive facilities and infrastructure. Meanwhile, externally, not all people know about Islamic banking and its products.